Metabolomic Differential Compounds Reflecting the Clinical Efficacy of Polyethylene Glycol Recombinant Human Growth Hormone in the Treatment of Childhood Growth Hormone Deficiency - Ji Li; Weiwei Pan; Jianqin Qian; Yan Ni; Junfen Fu; Junfen Fu; Shaoqing Ni; Shaoqing Ni (Frontiers Media S.A., 2022)
Understanding metabolite profiles may aid in providing a reference for individualized treatment using PEG-rhGH. Therefore, this study aimed to evaluate the clinical efficacy of PEG-rhGH in treating GHD patients by using a metabolomic approach. Fifty-seven pediatric participants treated with PEG-rhGH were enrolled (28 GHD patients with high clinical efficacy and 29 GHD patients with lower clinical efficacy). Serum samples from all patients were first collected at baseline for biochemical detection; then metabolite levels were measured using gas chromatography time-of-flight mass spectrometry. The candidates included heptadecanoic acid, stearic acid, 2-hydroxybutyric acid, myristic acid, palmitoleic acid, D-galactose, dodecanoic acid, and oleic acid. The related metabolic pathways involved fatty acid metabolism and energy metabolism. This study suggested that growth gains of PEG-rhGH treatment might be differentiated by altered serum levels of fatty acid. Collectively, the metabolomic study provides unique insights into the use of PEG-rhGH as a therapeutic strategy for individualized treatment.